2020
DOI: 10.1038/s41598-020-61026-x
|View full text |Cite
|
Sign up to set email alerts
|

A highly conserved complete accessory Escherichia coli type III secretion system 2 is widespread in bloodstream isolates of the ST69 lineage

Abstract: Bacterial type III secretion systems (T3SSs) play an important role in pathogenesis of Gram-negative infections. enteropathogenic and enterohemorrhagic Escherichia coli contain a well-defined T3SS but in addition a second T3SS termed E. coli T3SS 2 (ETT2) has been described in a number of strains of E. coli. the majority of pathogenic E. coli contain elements of a genetic locus encoding ETT2, but which has undergone significant mutational attrition rendering it without predicted function. Only a very few strai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Almost every strain in the ST69 complex, aside from E. coli CFS3269 and CFS3301, has eaeX, which encodes for an invasin/intimin-like large outer membrane protein [25]. The eaeX gene has also been identified in other ST69 E. coli [26]. According to previous reports, the increased serum survival gene iss and the closely related bor gene were commonly identified in bacteria linked with an extra-intestinal pathotype (ExPEC) and was also found in the case of bovine necrotoxigenic E. coli [27].…”
Section: Population Structure Sequencing and Analysis Of Gene Contentmentioning
confidence: 99%
“…Almost every strain in the ST69 complex, aside from E. coli CFS3269 and CFS3301, has eaeX, which encodes for an invasin/intimin-like large outer membrane protein [25]. The eaeX gene has also been identified in other ST69 E. coli [26]. According to previous reports, the increased serum survival gene iss and the closely related bor gene were commonly identified in bacteria linked with an extra-intestinal pathotype (ExPEC) and was also found in the case of bovine necrotoxigenic E. coli [27].…”
Section: Population Structure Sequencing and Analysis Of Gene Contentmentioning
confidence: 99%
“…ETT2 was more prevalent in DAEC (40%) than in tEAEC (12.5%) and was absent in all commensal strains ( Table 2 ). With exception of MEX-20 tEAEC genome, the whole ETT2 gene cluster was identified in all strains of clades I, II, III, g and h. It has been reported that ETT2 participates in the invasion of endothelial cells by NMEC strain EC10 (Yao et al, 2009 ) and may have functional importance in infection among human pathogenic E. coli strains isolated from blood samples (Fox et al, 2020 ). Aai-T6SS was only identified among tEAEC genomes ( P < 0.0001).…”
Section: Results and Discusionmentioning
confidence: 97%
“…The secretion system components have been studied extensively and have repprted in different animal pathogenic bacteria such as Pseudomonas aeruginosa (19, 20), Vibrio cholerae (21, 22), Salmonella sp. (23), Escherichia coli (24), Bacillus subtilis (25) etc. However, in depth reports regarding the components of secretion system on plant pathogens are scanty.…”
Section: Discussionmentioning
confidence: 99%